The Role of Disgust in Posttraumatic Stress: A Critical Review of the Empirical Literature. Issue 3 (9th July 2018) - Badour, Christal L.; Feldner, Matthew T.
The current review provides a detailed analysis of the burgeoning literature examining the role of disgust in understanding posttraumatic stress symptomatology. Research in this area generally converges to suggest (1) posttraumatic stress is associated with the experience of elevated disgust, (2) individual differences in disgust vulnerabilities may relate to increased posttraumatic stress symptom levels, (3) retrospective report of peritraumatic disgust is related to posttraumatic stress symptom levels, and (4) posttraumatic stress symptom levels appear to be associated with increased disgust, including in response to traumatic event cues. Importantly, much of this research suggests observed relations between disgust and posttraumatic stress are at least somewhat unique from relations between fear/anxiety and posttraumatic stress. Future research is now needed to identify mechanisms involved in these relations in order to inform the prevention and treatment of disgust-related posttraumatic stress disorder.